E-Engineering for Middle East and North Africa (MENA): Why and How - Ferreira, Paulo (2021)
The potential for development of the Middle East and North Africa region has as one of it's obstacles the lack of a suitable engineering workforce. The Higher Education Institutions of the area have e-Engineering (online Engineering Education using Remote Laboratories) a tool to increase the number and quality of graduated Engineers. The e-Lives project aims to disseminate e-Engineering (good practices) in the region, and has documents and knowledge that can help all interested in this task.